2015
DOI: 10.14202/vetworld.2015.121-124
|View full text |Cite
|
Sign up to set email alerts
|

Virulence genes detection of Salmonella serovars isolated from pork and slaughterhouse environment in Ahmedabad, Gujarat

Abstract: Aim:The aim was to detect virulence gene associated with the Salmonella serovars isolated from pork and Slaughterhouse environment.Materials and Methods:Salmonella isolates (n=37) used in this study were isolated from 270 pork and slaughter house environmental samples collected from the Ahmedabad Municipal Corporation Slaughter House, Ahmedabad, Gujarat, India. Salmonella serovars were isolated and identified as per BAM USFDA method and serotyped at National Salmonella and Escherichia Centre, Central Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
47
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 23 publications
(19 reference statements)
12
47
2
1
Order By: Relevance
“…Some studies reported the detection of this gene in all tested Salmonella spp. isolates [49][50][51][52][53][54][55][56][57][58]. On the other side, Moussa et al [59] and Maysa and Abd-Elall [60] couldn't find invA gene in all isolates, same as our study.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Some studies reported the detection of this gene in all tested Salmonella spp. isolates [49][50][51][52][53][54][55][56][57][58]. On the other side, Moussa et al [59] and Maysa and Abd-Elall [60] couldn't find invA gene in all isolates, same as our study.…”
Section: Resultssupporting
confidence: 84%
“…None of all 37 Salmonella isolated from pork and slaughterhouse by Chaudhary et al [57] possessed the spvC gene. This variable state suggested that the prevalence of Salmonella virulence plasmids is restricted within the isolates of some defined origin of sources.…”
Section: Resultsmentioning
confidence: 95%
“…High prevalence of inv A virulence gene in Salmonella serovars has also been reported by other workers [ 22 , 23 ]. We found inv A gene was 100% similar with other Salmonella serovars.…”
Section: Discussionsupporting
confidence: 78%
“…It has been reported that invA gene is present only in Salmonella species and therefore is used as a golden marker in genetic diagnosis of Salmonella species as previously described (O'Regan et al, 2008). In our study the invA gene was detected with 100% in all examined Salmonella serovars, high prevalence rates of invA virulence gene in Salmonella serovars has also been reported by other workers (Karmi, 2013 andChaudhary et al, 2015). In addition, the result of our study revealed that the stn gene was present in all of the isolates 100%.…”
Section: Discussionsupporting
confidence: 87%